Tradisi Cawisan dan Otoritas Religius Habaib dalam Pembentukan Citra Islam di Palembang pada Awal Abad ke-21 - Luthfi, Muhammad Ilmi; Syarifuddin, Syarifuddin; Yusuf, Syafruddin (Department of History, Faculty of Humanities, Diponegoro University, 2023)
This article discusses on the religious authority of the Habaib in Palembang, starting from the arrival of the Habaib, namely during the sultanate, post-sultanate periods and its relationship with the Cawisan culture in Palembang. Cawisan are joint dhikr activities, public lectures, recitations held in mosques, prayer rooms and other places devoted to religious learning. Interest in cawisan in Palembang during the New Orde experienced a decline for various reasons. In the end, the Habaib became the new authority in the midst of Palembang's Muslim community by actively teaching in the cawisan room at the beginning of the 21st century. The issues raised in this study are Cawisan culture in the early 21st century and the religious authority of Habaib in Cawisan culture in Palembang. This type of research is a qualitative approach and is carried out based on the right data through interviews with four informants namely Habib Mahdi Muhammad Syahab, Habib Ali Karror al-Haddad, Raden Muhammad Ikhsan, and Kemas Andi Syarifuddin. The results of this study indicate that the Habaib have a role accompanied by authority in the cawisan culture at the beginning of the 21st century while in the previous era the independent kiai were much more influential in the cawisan culture.